Bacteria Foraging Algorithm in Antenna Design - Biswa Binayak Mangaraj; Manas Ranjan Jena; Saumendra Kumar Mohanty (Applied Computational Intelligence and Soft Computing)
A simple design procedure to realize an optimum antenna using bacteria foraging algorithm (BFA) is proposed in this paper. The first antenna considered is imaginary. This antenna is optimized using the BFA along with a suitable fitness function formulated by considering some performance parameters and their best values. To justify the optimum design approach, one 12-element Yagi-Uda antenna is considered for an experiment. The optimized result of this antenna obtained using the optimization algorithm is compared with nonoptimized (conventional) result of the same antenna to appreciate the importance of optimization.